2016
DOI: 10.1515/ijme-2016-0020
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of Key Success Factors that Influence Business Performance: The Experiences of Women Micro-entrepreneurs from Mazovia Voivodeship of Poland

Abstract: Women-owned businesses are one of the fastest growing categories of firms in the world, but they are greatly understudied in countries from the Central and Eastern Europe (CEE) [Zapalska et al., 2005]. The purpose of this paper is to examine the relationship between business success predictors and the performance of female-owned micro-enterprises from the Mazovia Voivodeship in Poland during the period 2011-2013, using an Internet-based survey questionnaire. The data were collected by the CAWI (computer assist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
2
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 19 publications
(17 reference statements)
0
4
2
2
Order By: Relevance
“…In line with this, the current study is consistent with the research findings of Wangari (2017) who reported that women entrepreneurs who suffer capital constraints in their initial business investment have lower profits, and their survival rate is lower than those who had adequate capital. On the other side, the finding of this study contradicts with that of Leszczyński (2016) who stated that successful female business owners relied primarily on their own resources ("Financial capital") to fund their operational activities and the short-to medium-term growth needs of their firms. The study confirmed that access to business training is also statistically significant and has a positive association with women entrepreneurs' performance (Table 4).…”
Section: Econometric Results and Discussion On Performance Determinantscontrasting
confidence: 99%
“…In line with this, the current study is consistent with the research findings of Wangari (2017) who reported that women entrepreneurs who suffer capital constraints in their initial business investment have lower profits, and their survival rate is lower than those who had adequate capital. On the other side, the finding of this study contradicts with that of Leszczyński (2016) who stated that successful female business owners relied primarily on their own resources ("Financial capital") to fund their operational activities and the short-to medium-term growth needs of their firms. The study confirmed that access to business training is also statistically significant and has a positive association with women entrepreneurs' performance (Table 4).…”
Section: Econometric Results and Discussion On Performance Determinantscontrasting
confidence: 99%
“…In line with this, the current study is consistent with the research ndings of Wangari (2017) who reported that women entrepreneurs who suffer capital constraints in their initial business investment have lower pro ts, and their survival rate is lower than those who had adequate capital. On the other side, the nding of this study contradicts with that of Leszczyński (2016) who stated that successful female business owners relied primarily on their own resources ("Financial capital") to fund their operational activities and the short to medium-term growth needs of their rms.…”
Section: Econometric Results and Discussion On Performance Determinantscontrasting
confidence: 99%
“…This is very similar to that of motivation and as explained earlier One of the greatest factors that also impact women entrepreneur in Malaysia is the fact that most of them don't have any mentor or when they have a mentor, such mentors are not fully committed to them and so practically don't gain anything whatsoever and so hardly perform beyond a level even though they have the required skills, management skills and knowledge of how to run a successful business. Another twist to this is that, where the young entrepreneur has a committed mentor, her skills and initiatives can be improved over time which enhances the level of her performance and eventually transforms into business success which is the ultimate goal of being an entrepreneur to become successful (Leszczyński, 2016).…”
Section: Mentorshipmentioning
confidence: 99%